Isolation and characterization of tributyltin-resistant bacteria from contaminated surface sediment at Kong Kong Laut, Johor, Malaysia - Abussamad, Abubakar (2016)
Tributyltin (TBT) is a species of organotin compound (OTC) under butyltin (BT) group, used as antifouling biocide in boat and ships paints to prevents the attachments of marine organism on their hull surface. Tributytin is very toxic to variety of targeted and none targeted organisms and has high persistence in sediments (can stays for up to thirty (30) years). Despite its global ban in 2008 by the International Maritime Organization (IMO), high concentrations of TBT in sediments from fresh and marine waters in many places across the world including northwest coast of Portugal, Strait of Johore Malaysia, South Africa, Australia among others was reported years after the total global ban. Malaysia is one of the countries with busiest maritime activities and well documented with high level of TBT in the marine environments, thus there is an urgent need to remediate TBT contamination. This study aimed at isolating the best indigenous bacterial specie(s) from TBT and heavy metals contaminated sediment as a prospect in bioremediation of TBT contamination based on the TBT and heavy metals tolerance ability. Sediment samples were collected from TBT contaminated surface sediments of Kong Kong Laut area. Bacteria were isolated in Minimal Salt Media (MSM) and screened in different concentrations of TBT treated media (1000, 1200 and 1500 g/L). Selected TBT-resistant isolates were identified using morphological, biochemical (Gram staining) and polymerase chain reaction (16S rRNA) techniques. Growth tolerance of the best isolate was ascertained in MSM treated with different TBT (500, 1000, 1500, 2000 and 2500 g/L) and heavy metals (0, 1, 5, 15, 25, 40 and 100 mg/L) concentrations. The metals were copper, zinc, lead and cadmium. Thirty-five (35) bacterial colonies were isolated on MSM from the sediment samples. Fourteen (14) isolates (KK1, KK2, KK3, KK4, KK5, KK6, KK7, KK8, KK12, KK14, KK15, KK16, KK17 and KK18) were found to resisted 1000 g/L of TBT, a concentration level above the reported contaminated level (790 μg/L) at the sampling area. All the 14 isolates were Gram negative and three (3) isolates (KK1, KK3 and KK7) amongst were found to resisted TBT up to 1200 g/L. The 3 isolates were identified as Citrobacter sp. FIRD 1, Klebsiella sp. FIRD 2 and Acinetobacter sp. FIRD 3 with accession no KR027917, KR005669 and KR013742, respectively. This study managed to isolate, screened and identified. The best TBT-resistant bacterium from Kong Kong Laut area, named Klebsiella sp. FIRD 2, a new species with high growth tolerance against TBT (1500 μg/L) and heavy metals (Cu 25, Pb 40, Zn 100 and Cd 40 mg/L). This study established ii that Klebsiella sp. FIRD 2 isolated from Kong Kong Laut Johore has great potentials to be used as a bioremediation agent of TBT because of its high growth tolerance to TBT and heavy metals contaminated media.